Using a chimeric respiratory chain and EPR spectroscopy to determine the origin of semiquinone species previously assigned to mitochondrial complex I - John J. Wright (BMC Biology, 2020)
Abstract Background For decades, semiquinone intermediates have been suggested to play an essential role in catalysis by one of the most enigmatic proton-pumping enzymes, respiratory complex I, and different mechanisms have been proposed on their basis. However, the difficulty in investigating complex I semiquinones, due to the many different enzymes embedded in the inner mitochondrial membrane, has resulted in an ambiguous picture and no consensus. Results In this paper, we re-examine the highly debated origin of semiquinone species in mitochondrial membranes using a novel approach. Our combination of a semi-artificial chimeric respiratory chain with pulse EPR spectroscopy (HYSCORE) has enabled us to conclude, unambiguously and for the first time, that the majority of the semiquinones observed in mitochondrial membranes originate from complex III. We also identify a minor contribution from complex II. Conclusions We are unable to attribute any semiquinone signals unambiguously to complex I and, reconciling our observations with much of the previous literature, conclude that they are likely to have been misattributed to it. We note that, for this earlier work, the tools we have relied on here to deconvolute overlapping EPR signals were not available. Proposals for the mechanism of complex I based on the EPR signals of semiquinone species observed in mitochondrial membranes should thus be treated with caution until future work has succeeded in isolating any complex I semiquinone EPR spectroscopic signatures present.